A comparative study between fistulotomy and fistulectomy in management of low anal fistulae - R., Ganesan; K., Karunakaran; Anandan, Heber (International Surgery Journal, 2017)
Background: Fistula in ano is a silent menace in human beings, the treatment is a challenging one even for experienced surgeons, fistula in ano forms a good majority of treatable benign lesions of rectum and anal canal. Aim was to study the efficacy of fistulotomy and fistulectomy in the treatment of low anal fistulae. Methods: A randomized control study was conducted to compare fistulotomy with fistulectomy in patients with low anal fistulae. Results: The operating time in fistulotomy group was 12.13minutes±2.11minutes and in fistulectomy group was 22.23±3.36minutes. The post-surgery hospital stays in Group I was 1.80±0.66days and in Group II was 2.60±0.563 days. The wound healing time in Group I was 24.20±2.95 days which was considerably less when compared to patients in Group II where it was 31.50±4.34 days. Conclusions: Fistulotomy has a slight edge over fistulectomy in the treatment of low anal fistulas since it has shorter operating time, less post-operative pain, less complications, quicker wound healing time, less incontinence and a comparable recurrence rate.